Cost of the Diet (CoD) Tool: First Results from Indonesia and Applications for Policy Discussion on Food and Nutrition Security. Issue 2 (June 2013) - Baldi, Giulia; Martini, Elviyanti; Catharina, Maria; Muslimatun, Siti; Fahmida, Umi; Jahari, Abas Basuni; Hardinsyah,; Frega, Romeo; Geniez, Perrine; Grede, Nils; Minarto,; Bloem, Martin W.; et al.
Background: The Minimum Cost of a Nutritious Diet (MCNut) is the cost of a theoretical diet satisfying all nutrient requirements of a family at the lowest possible cost, based on availability, price, and nutrient content of local foods. A comparison with household expenditure shows the proportion of households that would be able to afford a nutritious diet. Objective: To explore using the Cost of Diet (CoD) tool for policy dialogue on food and nutrition security in Indonesia. Methods: From October 2011 to June 2012, market surveys collected data on food commodity availability and pricing in four provinces. Household composition and expenditure data were obtained from secondary data (SUSENAS 2010). Focus group discussions were conducted to better understand food consumption practices. Different types of fortified foods and distribution mechanisms were also modeled. Results: Stark differences were found among the four areas: in Timor Tengah Selatan, only 25% of households could afford to meet the nutrient requirements, whereas in urban Surabaya, 80% could. The prevalence rates of underweight and stunting among children under 5 years of age in the four areas were inversely correlated with the proportion of households that could afford a nutritious diet. The highest reduction in the cost of the child's diet was achieved by modeling provision of fortified blended food through Social Safety Nets. Rice fortification, subsidized or at commercial price, can greatly improve nutrient affordability for households. Conclusions: The CoD analysis is a useful entry point for discussions on constraints on achieving adequate nutrition in different areas and on possible ways to improve nutrition, including the use of special foods and different distribution strategies.